Leadership Succession and Strategic Change in Nigerian Commercial Banks - Badara, Abdulkadir Musa; ., Tan Fee Yean (Journal of Education and Vocational Research, 2013)
The relationship between leadership succession and strategic change is generally examined. However, more needs to be covered in the area. The paper proposed to provide a framework that will examine the relationship between leadership succession and strategic change in the Nigerian Banking sector. The model will help to a better understanding of the direct relationship between leadership succession and strategic change, hence, regulatory agencies, shareholders and board members, as well as management team will benefit from the study outcome.